BENTHIC MACROINVERTEBRATES AS A BIO INDICATOR FOR WATER QUALITY IN TAMASI LAKE TAHSIL BHADRAVATI DIST. CHANDRAPUR - Tekade R.S,; Telkhade P.M, (The Bioscan, 2025)
Benthic macroinvertebrates serve as effective bioindicators of water quality due to their sensitivity to environmental changes and their crucial role in aquatic ecosystems.Benthic macroinvertebrates act as biosensors, reflecting changes in water quality and ecosystem stability. Seasonal and spatial variations were analysed alongside key physicochemical parameters. Study area was Tamasi Lake, Tamasi Rt village, located in Bhadravati tehsil of Chandrapur district in Maharashtra, India.This st udy examines benthos diversity in Tamasi lake over a two year period Jan 2023 December 2024 to assess ecological health and water quality. In present investigation total of 44 macro invertebrate species were recorded and identified, from 4 Phylum ,18 Order s and 30 Families from all the study sites. The Phylum Mollusca of macro invertebrates showed their maximum appearance with 17 species, The present study concludes that Benthic community that shows changes in diversity pattern. The diversity of species at all the four sampling sites shows that lake water is suitable for benthic organisms.